2013
DOI: 10.1371/journal.pone.0060473
|View full text |Cite
|
Sign up to set email alerts
|

BMP2 Genetically Engineered MSCs and EPCs Promote Vascularized Bone Regeneration in Rat Critical-Sized Calvarial Bone Defects

Abstract: Current clinical therapies for critical-sized bone defects (CSBDs) remain far from ideal. Previous studies have demonstrated that engineering bone tissue using mesenchymal stem cells (MSCs) is feasible. However, this approach is not effective for CSBDs due to inadequate vascularization. In our previous study, we have developed an injectable and porous nano calcium sulfate/alginate (nCS/A) scaffold and demonstrated that nCS/A composition is biocompatible and has proper biodegradability for bone regeneration. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 65 publications
5
110
1
Order By: Relevance
“…3 MSCs were infected with Ad-BMP2 in a serum-free medium for 4 h and then cultured overnight in the alpha-MEM medium with 2% FBS. 4 Scaffold preparation nCS was produced following the method reported previously. 36,37 Briefly, alginate was dissolved in PBS to prepare 10% alginate solution (pH 7.2).…”
Section: Preparation Of Bmp2 Genetically Engineered Mouse Mscs (M/b2)mentioning
confidence: 99%
See 3 more Smart Citations
“…3 MSCs were infected with Ad-BMP2 in a serum-free medium for 4 h and then cultured overnight in the alpha-MEM medium with 2% FBS. 4 Scaffold preparation nCS was produced following the method reported previously. 36,37 Briefly, alginate was dissolved in PBS to prepare 10% alginate solution (pH 7.2).…”
Section: Preparation Of Bmp2 Genetically Engineered Mouse Mscs (M/b2)mentioning
confidence: 99%
“…Recent work from our laboratory demonstrated that bone marrow-derived MSCs (BM-MSCs) engineered to overexpress bone morphogenic protein 2 (BMP2) have greater bone formation potential than native MSCs. 3,4 BMPs are potent morphogens that stimulate bone formation in developed tissues 5,6 and one member of the family, BMP2, has shown promising results in orthopedic clinical trials. In addition to soluble signals, the mechanical properties of the scaffold have been shown to affect bone formation and surface stiffness has been shown to affect stem cell fate, [7][8][9][10] with harder/stiffer surfaces promoting osteogenic differentiation of MSCs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bmp2-gene-modified MSCs and EPCs were delivered in injectable calcium sulfate/alginate scaffolds, providing drastic increases in osteoblast differentiation and endothelial differentiation, resulting in increased bone and vascular formation. 101 Another genetic modification strategy involved modifying MSCs to express VEGF. 102 The increased expression of VEGF led to a threefold increase of vascular density compared with control MSC-seeded grafts.…”
Section: Genetic Modification Of Mscsmentioning
confidence: 99%